An automated platform for accelerating and focusing adaptive laboratory evolution - Ruppen, Peter; Bahls, Maximilian Ole; Gerlt, Michael Sebastian ; 0000-0003-2861-7435; Edelmann, Martin Peter; Roberts, Tania Michelle; Marlière, Philippe; Panke, Sven (Metabolic Engineering, 2026)
The rate of change in adaptive laboratory evolution (ALE), in which a population of microorganisms is continuously cultivated under a specific selective pressure, is controlled by the cellular mutagenesis rate and the randomness of where in the genetic material mutations are introduced. The constant selection pressure makes it a crucial, yet slow, method in developing microorganisms with novel phenotypes for which a rational engineering pathway is either too complex or unknown. A variety of targeted genome editing methods to accelerate evolution and facilitate the engineering of complex novel traits are available. However, these protocols require (nearly) as many successive transformation steps as loci they target, leaving the actual engineering process quite labor-intense, cumbersome, and at odds with the continuous nature of ALE. Here, we provide a fully integrated microfluidic platform that automates and accelerates bacterial transformation by electroporation to the mere push of a button. We demonstrate the functionality and effect by using oligonucleotide-directed mutagenesis in an ALE experiment to accelerate the engineering of riboflavin prototrophy into Escherichia coli .
Publisher Copyright: © 2025 The Authors.
Keywords: Automation; E. coli; Electroporation; Genome editing; Medium exchange; Microfluidics; Transformation